Indonesian Foreign Policy on Covid-19 Vaccine Procurement - Deasy Silvya Sari; Mas Halimah Mas Halimah; Akim Akim; Ali Zahid Habibullah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
This study aimed to explain Indonesia's foreign policy on Covid-19 vaccine procurement. It applied foreign policy concepts and qualitative methods to direct, collect, and analyze data. The data were collected through focus group discussions and structured interviews. The results showed that Indonesia's foreign policy on Covid-19 management had a national interest in protecting the public from contracting the virus. The country had 10 vaccines, including Sinovac, AstraZeneca, Pfizer, Moderna, Sinopharm, Johnson & Johnson, Sputnik V, CanSino, Novavax, and Zifivax. The procurement of the Covid-19 vaccine is carried out through bilateral and multilateral channels. The vaccine procurement financing was through buying and grants. The granting countries included China, Japan, the Netherlands, the United States, and the United Arab Emirates; while Covax Facility provided the multilateral grant.